Correlation between Cognitive Functions and Activity of Daily Living among Post-Stroke Patients - Prakoso, Kurniawan; Vitriana, Vitriana; Ong, Anam (Althea Medical Journal, 2016)
Background: Cognitive impairment is one of the most common post-stroke complications; however, neither patients nor health professionals are often aware of this complication. The impact of cognitive impairment on quality of life is reflected through basic activity daily living (bADL) and instrumental activity daily living (IADL). Prior studies concerning the correlation between cognitive impairment and activity daily living has shown contradictive results. This study was conducted in order to analyze the correlation between the cognitive functions and activity daily living in post stroke patients at Dr. Hasan Sadikin General Hospital.Methods: This cross-sectional study was carried out to 23 post-stroke patients from SeptemberâNovember 2015. Samples were collected through consecutive sampling at Dr. Hasan Sadikin General Hospital. Mini Mental State Examination (MMSE) was used to assess the cognitive functions and Lawton and Brody Scale to assess both bADL and IADL. Spearman correlation was selected to analyze the existing correlation between each cognitive domain and activity daily living.Results: Spearman statistical correlation showed an insignificant correlation between the cognitive functions and bADL (r2=0.181, p=0.408) and a significant correlation with IADL was obtained (r2=0.517, p=0.03). The only cognitive domain positively correlated with IADL was orientation to time and verbal recall.Conclusions: There is a correlation between cognitive functions and IADL among post-stroke patients at Dr. Hasan Sadikin General Hospital. [AMJ.2016;3(3):329â33]Â DOI: 10.15850/amj.v3n3.874